Description of Respondent Characteristics and Risk Factors for Tuberculosis (TB) Incidence at the Rancaekek Community Health Center, Bandung Regency in 2025 - Yusuf, Yusnan (LPPM Universitas Mohammad Husni Thamrin, 2026)
Tuberculosis (TB) remains a serious public health problem in Indonesia, particularly in West Java Province. Rancaekek Subdistrict has the highest number of TB cases in Bandung Regency, with 303 cases reported in 2020. This study aimed to describe the characteristics of respondents and risk factors associated with TB incidence at the Rancaekek Public Health Center. A case-control study design was used with a total sample of 60 respondents, consisting of 20 cases and 40 controls. Data were collected through interviews using a structured questionnaire and analyzed using univariate analysis. The results showed that the majority of respondents were aged 25–45 years (53.3%), male (56.7%), lived in high-density housing (60.0%), had inadequate house ventilation (53.3%), and poor lighting conditions (51.7%). In addition, most respondents had smoking habits (56.7%), and 40.0% had a history of contact with TB patients. A total of 33.3% of respondents were TB cases. In conclusion, demographic characteristics, housing environmental conditions, and behavioral factors have the potential to contribute to TB incidence. Therefore, strengthening environmental health promotion, improving housing conditions, and enhancing community education are necessary to reduce the risk of TB transmission in the study area.